Підготовка викладача до диференційованого навчання студентів економічних спеціальностей - Гоцуляк, К. І.; Ємець, О. І.; Hotsulyak, K. I.; Yemets, O. I. (Видавництво Львівської політехніки, 2017)
Розглянуто методологічне підґрунття підготовки викладача до диференційованого навчання студентів економічних спеціальностей. На підставі з’ясованих особливостей підготовки викладача до диференціації навчання студентів економічних спеціальностей, доведена важливість та необхідність його професійного розвитку та самовдосконалення щодо використання інноваційних технологій навчання, зокрема диференційованого навчання

The methodological basis of teacher training to differentiated training of students of economic specialties is considered. On the basis of the clarified features of teacher training to differentiate the training of students of economic specialties, the importance and necessity of its professional development and self-improvement in the use of innovative teaching technologies, in particular, differentiated learning, has been proved. The reviewed acticle trained teacher differentiated instruction to a problem of general; grounded methodological guidance of teacher training education differentiated instruction to students of economic specialties; reveals the essential characteristics of differentiated teaching students in a modern institution. The purpose of the article is to identify, study and experimental verification efficiency pedagogical conditions of preparation of the teacher differentiated instruction to students of economics. The object of study – the training of teachers in the system of teacher education. The subject of research – pedagogical conditions of training of teachers in the system of teacher education to students differentiated. Based on teacher training the features shown the importance and necessity of its professional development and learning about the use of innovative learning technologies, including differentiated instruction. Emphasized that the decisive factor in the revival of cultural and creative function of the institution, humanization and democratization of the educational process is the differentiation of training that provides the maximum development of students of all ability levels, the disclosure of their identity (the psychological aspect), effective use of their capacity for learning self ( pedagogical aspect). The analysis of psychological and educational literature and teacher training features gave reason to conclude that successful implementation of the ideas of differentiation of instruction in schools should be revised organizational, semantic and technological components of teacher preparation in terms of teacher education. In particular, the content needs to be updated curriculum courses for teachers according to educational standards and the needs of modern education. The results of the formation of the stage of the experiment confirmed the legitimacy and effectiveness of the proposed learning conditions and the model of training of teachers, differentiated learning for students gives reason to believe that the purpose of the study is achieved. Based on the research proved theoretically and practically solved the problem of teacher training in the education system of differentiated instruction to students. The study does not cover all aspects related to the preparation of the teacher differentiated instruction to students. Prospects for further research see in training of the general education in postsecondary education organizations to provide differentiated instruction in basic and specialized schools.
Preparation teachers to differentiated instruction students of economic specialties
Keywords: диференційоване навчання студентів; підготовка викладачів; формування готовності викладача; педагогічні умови; диференціація; differentiated student learning; teacher training; teacher readiness formation; pedagogical conditions; differentiation; 371.13; 371; 14; 372.4